PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM PENANGANAN PENGUNGSI TIMUR LESTE DI INDONESIA PASCA REFERENDUM TAHUN 1999 HINGGA 2005 - Muhammad Al-Harits; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This whole scientific research has a goals, the main goals of this research is to make sure that refugee has a living in Indonesia that not only place but also has a humanitarian help from the organization that named UNHCR. Who shared a medical belongings and also a place to live. This research use the Clive Archer Theory that contains independence actor whos sounds that only organization that controls it’s one and only paradigm, if it’s paradigm works in a way it means that there’s no one power outhere can limited that organization vision. Once Organization said that there’s no other intervention can contact the organization. This research also use the qualitative theory that brings from books from library and website in the Internet. The results of this study are that this study describes the successful role of UNHCR in providing comfort to refugees from Timor Leste to Indonesia. They got medicines and evacuation posts in Indonesia. This is a comprehensive step in addressing these refugees and this research also shows that the role and policies carried out by UNHCR in dealing with the problem of East Timorese refugees in Indonesia are repatriation (repatriation), resettlement (resettlement), Local integration (reintegration/integration with the community during the post-displacement period). Keywords : Referendum, Timor Leste, Indonesia, Refugees, UNHCR